(Re) apropriando a centralidade na metrópole - Janaína Marx Pinheiro (2014)
It is suggested a reflection on urban centrality, its concepts and its production here analyzed from the lefebvrian perspective on the social production of space. Therefore, as well as linked to the existing relations of production, can only be understood in the context of a particular society. The aim is to demonstrate the importance of the centrality and also expose their conflicts within the capitalist mode of production that has appeared increasingly intense. Thus, as Lefebvre proposes, also considers the urban as the horizon, illuminating virtuality, and the centrality the essence of this urban. But, what centrality Lefebvre speaks? This question is the heart of this work. However, instead of finding closed answers or 'recipes' for this centrality the hypotheses are seeking provoke discussion and propose an speculative approach about the centrality produced by urban society.